Boris Mironov; edited by Gregory L. Freeze. The Standard of Living and Revolutions in Imperial Russia, 1700-1917. New York, Routledge, 2012, XXXII+668 págs., ISBN: 978-041-560-854-1. - Martínez Carrión, José Miguel (Investigaciones de Historia Económica, 2019)
Sin resumen